Meritocracy in Singapore as an alternative modernisation project - Akylbay, А. (Journal of Oriental Studies, 2023)
This article examines the phenomenon of political meritocracy, the true embodiment of which can be attributed to the history of Singapore's political system formation and development. Analysis of various modernisation projects is still topical to thoroughly analyse them, and form conclusions that can be applied to the development of other states. The methodological basis of study is both historical and political science research methods. The first category includes descriptive and narrative, historical and genetic methods, the second category includes structural and functional, value and normative methods, and also a systematic approach. Today the research studies the state of Singapore, analyses political, economic, and attitudinal prerequisites for establishing meritocracy as a leading concept in the country, and presents the main value orientations shaping Singapore's political process. The article focuses on the analysis of similarities and differences between the main ideological benchmarks that are common to countries of the “collective West” as well as those in Asia, particularly in its South-East part. The case of Singapore is used as an example to analyse the emergence and spread of meritocracy in the practice of public administration in Asian countries. Besides, moral and ethical nuclear concepts which ensure the functioning of the public administration system in Singapore are revealed. The information presented in this article will be of interest to researchers in comparative political science and regional studies, and also to a wide range of readers whose interests are directly related to the topic considered in this study. Keywords: Meritocracy, Singapore, modernisation, South-East Asia, oriental studies, comparative political science.